2006
DOI: 10.1111/j.1365-4632.2004.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid in a patient with psoriasis during the course of PUVA therapy: study by ELISA test

Abstract: A 65-year-old woman had a history of deep vein thrombosis and depression. Psoriasis was diagnosed in 1986 and various topical and systemic therapies, singly or in combination, were prescribed: tar, topical corticosteroids, cyclosporine, etretinate, and methotrexate. Two courses of oral and one course of bath psoralen plus UVA (PUVA) therapy (cumulative dose, 467 J/cm(2)) and UVB (2.96 J/cm(2)) had been given. In January 1999, she developed a flare of generalized psoriasis. In May 1999, therapy with PUVA (8-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
22
0
3
Order By: Relevance
“…Psoralen ultraviolet A (PUVA) [90], narrowband ultraviolet B phototherapy (NBUVB) and photodynamic therapy (PDT) can induce typical and atypical, localized or generalized forms of BP. Rakvit et al reported a case of localized BP induced by PDT [91] and Chan et al reported a case of generalized lichen planus pemphigoides induced by NBUVB therapy [92].…”
Section: Atypical Presentations Of Bullous Pemphigoidmentioning
confidence: 99%
“…Psoralen ultraviolet A (PUVA) [90], narrowband ultraviolet B phototherapy (NBUVB) and photodynamic therapy (PDT) can induce typical and atypical, localized or generalized forms of BP. Rakvit et al reported a case of localized BP induced by PDT [91] and Chan et al reported a case of generalized lichen planus pemphigoides induced by NBUVB therapy [92].…”
Section: Atypical Presentations Of Bullous Pemphigoidmentioning
confidence: 99%
“…So such changes may induce the production of BP autoantibodies by polyclonal activation of B cells [1]. On the other hand, PUVA may also alter the immunologic reactivity of T-helper and T-suppressor cells that may result in the development of the autoantibodies against native proteins [6]. Inversely, the protective effect of UVB irradiation has been showed by reducing the expression of pemphigoid antigens in organ-cultured normal human skin in a study [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to generalize about the prognosis of PUVA induced BP because of the limited numbers of cases [5], it seems that its prognosis is better with mild and transient behavior than idiopathic ones [6]. …”
Section: Discussionmentioning
confidence: 99%
“…[10] Reduced barrier function of the diseased psoriatic epidermis, combined with the irritant effects of therapies administered for psoriasis, such as anthralin, tar, and ultraviolet light, together with a low-grade immunologic BMZ insult, may precipitate blister formation. [7] Cram and Fukuyama demonstrated the triggering role of ultraviolet light B (UVB) in the induction of BP. [12] Psoralen and ultraviolet light A (PUVA) therapy is also known to induce blisters mimicking BP.…”
Section: Discussionmentioning
confidence: 99%